Effect of radiotherapy on freedom from seizures in dogs with brain tumors. (7th February 2020) - Monforte Monteiro, Susana R.; Rossmeisl, John H.; Russell, Jason; Holmes, Mark A.; Wessmann, Annette; Morris, Jo; Dobson, Jane M.; Vanhaesebrouck, An E.
Abstract: Background: Seizures are a common presenting sign in dogs with brain tumors. Hypothesis/Objectives: To investigate the effect of radiotherapy on freedom from brain tumor‐associated seizures and survival time in dogs. Animals: Thirty‐two client‐owned dogs with brain tumor‐associated seizures; 18 received medical treatment and radiotherapy, 14 received medical treatment alone. Methods: Multicenter retrospective study. Baseline characteristics (seizure semiology, magnetic resonance imaging [MRI] characteristics, and treatment) and duration of seizure freedom were recorded for the 2 treatment groups. Duration of seizure freedom between groups was compared (log‐rank test) using Cox's proportional hazard analysis, with baseline characteristics entered as covariates. Results: The duration of seizure freedom and survival time were significantly longer in the radiotherapy group ( P < .001), with a mean of 24 months (95% confidence interval [CI], 14.3‐33.8) versus 1.7 months in the control group (95% CI, 0.5‐2.9) and a mean of 34.6 months (95% CI: 25.2‐44.1) versus 6.2 months in the control group (95% CI, 2.6‐9.7) respectively. Baseline characteristics were not associated with duration of seizure freedom after the start of treatment. In the radiotherapy group, 5 dogs were euthanized during the study period because of causes other than seizures. In the control group, recurrence of seizures was observed before death in all dogs. Conclusions and Clinical Importance: A longer period of seizure freedom and longer survival time was observed in dogs with brain tumors after radiotherapy compared to medical treatment only. The pathophysiological mechanisms of epileptogenesis and the effect of radiation therapy on seizure control are unclear to date. Further prospective studies are needed.